Ecosystem service information to benefit sustainability standards for commodity supply chains. Issue 1 (October 2015) - Chaplin‐Kramer, Rebecca; Jonell, Malin; Guerry, Anne; Lambin, Eric F.; Morgan, Alexis J.; Pennington, Derric; Smith, Nathan; Franch, Jane Atkins; Polasky, Stephen
Abstract : The growing base of information about ecosystem services generated by ecologists, economists, and other scientists could improve the implementation, monitoring, and evaluation of commodity‐sourcing standards being adopted by corporations to mitigate risk in their supply chains and achieve sustainability goals. This review examines various ways that information about ecosystem services could facilitate compliance with and auditing of commodity‐sourcing standards. We also identify gaps in the current state of knowledge on the ecological effectiveness of sustainability standards and demonstrate how ecosystem‐service information could complement existing monitoring efforts to build credible evidence. This paper is a call to the ecosystem‐service scientists to engage in this decision context and tailor the information they are generating to the needs of the standards community, which we argue would offer greater efficiency of standards implementation for producers and enhanced effectiveness for standard scheme owners and corporations, and should thus lead to more sustainable outcomes for people and nature.